Cost‐effectiveness of a behavioral intervention for persistent urinary incontinence in prostate cancer patients. Issue 4 (12th May 2015) - Zhang, Amy Y.; Fu, Alex Z.
Abstract: Objective: The aim of this study was to evaluate the cost‐effectiveness of a behavioral intervention for urinary incontinence of prostate cancer patients. Study subjects were either participating in or eligible but declined (i.e., nonparticipating) the active intervention study. Methods: The intervention‐participating subjects were randomized into three groups, including two intervention groups (support and telephone groups) and a usual care reference group. Intervention‐nonparticipating subjects were concurrently enrolled. Intervention effectiveness was assessed on the EQ‐5D measure. The costs included direct healthcare cost from medical billing data, patient out‐of‐pocket expense, caregiver expense, patient loss‐of‐work cost, and intervention cost. We calculated incremental cost‐effectiveness ratios (ICERs) from societal, provider, and patient perspectives. Results: Two hundred and sixty‐seven intervention‐participating and 69 intervention‐nonparticipating post‐cancer treatment patients were included. The support and telephone groups, but not the usual care group, had significantly higher EQ‐5D index scores (0.054, p  = 0.033, and 0.057, p  = 0.026, respectively) than the intervention‐nonparticipating group at month 6. Within 6 months, intervention cost per subject was $252 and $484, respectively, for providers, and $564 and $203, respectively, for the support and phone group subjects. The final ICERs were $16, 759 per quality‐adjusted life year (QALY) and $12, 561/QALY for support and telephone groups, compared with those of the intervention‐nonparticipating group. These ICERs are much smaller than $50, 000/QALY, the consensus threshold to determine cost‐effectiveness for society. Conclusions: The study interventions are cost‐effective in consideration of eligible patients who declined the interventions. The interventions can provide meaningful outcome improvement on urinary continence at a low cost. This evidence provides critical information for future health policy decision‐making of healthcare providers and payers. Copyright © 2015 John Wiley & Sons, Ltd.